KEPUASAN KONSUMEN TERHADAP PEMASARAN KONVENSIONAL DAN ONLINE MINUMAN KOPI DI DOESOEN COFFEE & SPACE BANDAR LAMPUNG - Moh. Daffa AP Hernanda; Dyah Aring Hepiana Lestari; Yuliana Saleh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
This study aimed  to determine consumer satisfaction toward the conventional and online marketing of coffee drink at Doesoen Coffee & Space Bandar Lampung. A survey method was employed involving 64 respondents, consisting of 32 conventional consumers and 32 online consumers. Conventional consumers were selected using accidental sampling from visitors who purchased products directly at Doesoen Coffee & Space, while online consumers were selected through purposive sampling based on information provided by the business management. Data were collected from July to August 2023. Validity and reliability tests were  used to determine whether research questionnaires were  valid and reliable. Data were analyzed using Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The atributes examined consisted of the seven components (7P) of the conventional marketing mix, including product, price, place, promotion, people, process, and physical evidence, as well as five components (5P) of  online marketing mix, namely e-product, e-price, e-process, e-place, and e-promotion. The CSI value of 7P conventional marketing was 89.39% and 5P online marketing was 88.23%. The conventional marketing attributes that  required  improvement were included price affordability, convenience and speed of payment, employee responsiveness in handling consumer complaints, and the efficiency of cashier service processes. Attributes that must be maintained were   the coffee taste, price quotes based on quality, strategic locations, cleanliness and comfortable cafes, consumer service, complete facilities, availability and cleanliness of toilets and prayer rooms, and attractive café appearance. The attributes of online marketing that need to be improved were  physical reality, product photos that have high resolution, and consumer information protection. Attributes that must be maintained were  product photos, product display, flavor variants, ease of transaction, various payment methods, and promotions.   Key words: Coffee drink, CSI, IPA